The Role of Ecological Mediation in Government in Realizing Governance Responsive Local Government in Baubau City - Muh. Askal Basir (STABN RADEN WIJAYA WONOGIRI, 2025)
This study aims to analyze the role of government ecology as a mediating variable in the relationship between digital public participation and government digitalization towards responsive local governance in Baubau City. The background of this study is based on the increasing public demand for fast, adaptive, and technology-based public services, which has not been fully balanced by the readiness of the local government ecosystem. This study uses a quantitative approach with the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method . Data were collected through a survey of 100 respondents from local government agencies and related stakeholders, with research instruments that have met the criteria of validity and reliability.The analysis results show that digital public participation has a significant impact on responsive governance and has a very strong influence on government ecology. Government digitalization is also proven to have a significant direct impact on responsive governance, but does not significantly affect government ecology. Furthermore, government ecology has a significant impact on responsive governance and acts as a mediating variable that strengthens the influence of digital public participation and government digitalization on governance responsiveness. These findings confirm that the success of digital transformation of local government is not only determined by technological aspects, but is highly dependent on the quality of the government ecosystem that includes the integration of actors, processes, and institutions. This research provides theoretical contributions to the development of digital governance studies based on a government ecology approach, as well as practical implications for local governments in formulating more holistic, collaborative, and sustainable digital transformation policies.